Agribusiness development strategy of papaya calina (carica papaya l.) - Yoesdiarti, Arti; Himmatul Miftah; Novita Yulanda (Jurnal Pertanian, 2023)
Papaya Calina (Carica papaya L.) is one of the main commodities in Cidolog Village, Cidolog District, Sukabumi Regency. Since 2020, Papaya plantation in Cidolog has remained static, and production has even decreased in 2020-2021 while national production increased. The research was conducted in December 2021 to identify the internal and external conditions in papaya agribusiness in Cidolog, and formulate strategies to develop the business. Internal and external environment mapping was obtained through observation and in-depth interviews with the farmer group. Assessment of the IFE and EFE matrices, and strategy formulation using SWOT Matrix, were obtained from interviews with five experts. Environment analysis shows that the papaya agribusiness in Cidolog Village has prospects for further development with an IFE value of 2.51 and an EFE of 2.64. The position of Calina's papaya agribusiness in IE matric is in cell 5 with a “guard and sustain” strategy. SWOT Matrix formulates 8 strategies namely 1) Expansion of land, 2) Increasing the role and dynamics of farmer groups, 3) Strengthening capabilities and access to networking, 4) Processing of inferior papaya into processed products, 5) Expansion of information and promotion of Papaya Calina Cidolog on the village website, District website, social media, and exhibitions, 6) Training on pest and plant disease control and cultivation practices in general, 7) Proposing road repairment to the relevant local government, and 8) opening the new market to supermarkets and a fruit shop.